Synthesis and morphology of iron–iron oxide core–shell nanoparticles produced by high pressure gas condensation. (18th April 2016) - Xing, Lijuan; ten Brink, Gert H; Chen, Bin; Schmidt, Franz P; Haberfehlner, Georg; Hofer, Ferdinand; Kooi, Bart J; Palasantzas, George
Abstract: Core–shell structured Fe nanoparticles (NPs) produced by high pressure magnetron sputtering gas condensation were studied using transmission electron microscopy (TEM) techniques, electron diffraction, electron energy-loss spectroscopy (EELS), tomographic reconstruction, and Wulff shape construction analysis. The core–shell structure, which is composed of an Fe core surrounded by a maghemite ( γ -Fe2 O3 ) and/or magnetite (Fe3 O4 ) shell, was confirmed by fast Fourier transform (FFT) analysis combined with EELS. It was found that the particle size and shape strongly depend on the gas environment. Moreover, extensive analysis showed that NPs with a size between 10–20 nm possess a truncated cubic morphology, which is confined by the 6 100 planes that are truncated by the 12 110 planes at different degrees. For NPs larger than 20 nm, the rhombic dodecahedron defined by the 12 110 planes is the predominant crystal shape, while truncated rhombic dodecahedrons, as well as non-truncated and truncated cubic NPs, were also observed. The NPs without truncation showed a characteristic inward relaxation indicating that besides thermodynamics kinetics also plays a crucial role during particle growth.